Exploring mothers’anxiety experiences and perceptions in accessing mental health support from pregnancy through the first two years postpartum - Idealistiana, Lia; Afrianti, Lisa; Afriansih, Luvvia; Riskana, Nesa Pertama; Nurseha, Saripah; Anggraeni, Eli (Alma Ata University Press, 2025)
Background: Changes during pregnancy can cause physical and psychological symptoms, such as anxiety. However, many mothers do not undergo mental health condition detection by healthcare professionals, often due to misconceptions or lack of awareness. Objectives: This study aims to analyze the relationship between mothers’ experiences and perceptions in seeking mental health support during pregnancy and up to two years postpartum.Methods: The design of this study is a retrospective cohort. The sample consisted of 249 respondents. The research was conducted in December 2024 at Karang Kitri Public Health Center, Sriamur Public Health Center, and the practices of midwives Luvvia Afriansid, Anita, Hj. Fitri, and Srimahi Public Health Center. The dependent variable was the experience of mental health problems, particularly anxiety, from pregnancy until two years postpartum. Statistical analysis was performed using multivariate logistic regression. Mothers’ perceptions of mental health detection were measured using the Mental Health Seeking Questionnaire, and anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HAM-A). The relationship between the two variables was analyzed using multivariate logistic regression.Results: The analysis showed that prior experience of mental health problems (particularly anxiety) did not significantly affect mothers’ perceptions of the importance of mental health detection (p = 0.142; p > 0.05). However, education level was significantly related to perception (p = 0.023; OR = 0.09), indicating that lower education levels are associated with lower positive perceptions toward mental health detection. Conclusions: The study revealed no significant relationship between maternal anxiety and perceptions of seeking mental health support, as many mothers experiencing moderate to severe anxiety did not recognize their symptoms as a mental health concern or seek professional help